Effects of Different Doses of Rocuronium for Facilitation of Endotracheal Intubation among the Patients Undergoing General Anaesthesia - Al-Arafath, Hasan; Begum, Muslema; Haque, AKM Ashraful; Bhuiyan, Md Jamil Siddiky; Ahmed, Md Towkir (Medicine Today, 2026)
Introduction: Endotracheal intubation is an integral part of airway management duringgeneral anesthesia. With the advancement of anesthesia, there have always been a search of an ideal muscle relaxants which can provide ideal intubating conditions in short duration with minimal side effects. Rocuronium is an intermediate acting Non- depolarising Muscle Relaxant (NDMR) with rapid onset of action. The aim of this prospective observational study was to assess and compare the time of onset of action and intubating conditions with three different doses of rocuronium bromide (0.6 mg/kg, 0.75 mg/kg, 0.9 mg/kg). Material and Methods: This study was conducted to compare and evaluate effect of three different doses of Rocuronium bromide for endotracheal intubation in ASA I & II patients aged 18-60 years of either sex. Patients were randomly allocated into three groups according to dose of Rocuronium (Group A - 0.6 mg/kg of Rocuronium bromide, Group B - 0.75 mg/kg of Rocuronium bromide & Group C – 0.90 mg/kg of Rocuronium bromide). Jaw relaxation, vocal cord position, motor response to intubation and overall intubating conditions were assessed. Results: Laryngoscopy and endotracheal intubation in each group were assessed by Cooper 1 criteria. Good to excellent intubating conditions were seen in 51%, 100% and 100% of the patients after 0.6 mg/kg, 0.75mg/kg, 0.9 mg/ kg of Rocuronium respectively. Onset of action were dose dependant. Conclusion: Lower, safe and sufficient dose of rocuronium bromide 0.75 mg/kg IV can produce good to excellent intubating conditions with rapid onset of action in contrast of a dose of 0.60 mg/kg IV and 0.90 mg/kg IV. Medicine Today 2026, Vol.38 (1): 71-75